Acute volume loading and exercise capacity in postural tachycardia syndrome - Figueroa, Rocío A. (American Physiological Society, 2014)
Postural tachycardia syndrome (POTS) is associated with exercise intolerance, hypovolemia, and cardiac atrophy, which may contribute to reduced stroke volume and compensatory exaggerated heart rate (HR) increases. Acute volume loading with intravenous (iv) saline reduces HR and improves orthostatic tolerance and symptoms in POTS, but its effect on exercise capacity is unknown. In this study, we determined the effect of iv saline infusion on peak exercise capacity (V̇o(2peak)) in POTS. Nineteen patients with POTS participated in a sequential study. V̇o(2peak) was measured on two separate study days, following administration of placebo or 1 liter of iv saline (NaCl 0.9%). Patients exercised on a semirecumbent bicycle with resistance increased by 25 W every 2 min until maximal effort was achieved. Patients exhibited blood volume deficits (−13.4 ± 1.4% ideal volume), consistent with mild to moderate hypovolemia. At baseline, saline significantly increased stroke volume (saline 80 ± 8 ml vs. placebo 64 ± 4 ml; P = 0.010), increased cardiac output (saline 6.9 ± 0.5 liter/min vs. placebo 5.7 ± 0.2 liter/min; P = 0.021), and reduced systemic vascular resistance (saline 992.6 ± 70.0 dyn-s/cm(5) vs. placebo 1,184.0 ± 50.8 dyn-s/cm(5); P = 0.011), with no effect on HR or blood pressure. During exercise, saline did not produce differences in V̇o(2peak) (saline 26.3 ± 1.2 mg·kg(−1)·min(−1) vs. placebo 27.7 ± 1.8 mg·kg(−1)·min(−1); P = 0.615), peak HR [saline 174 ± 4 beats per minute (bpm) vs. placebo 175 ± 3 bpm; P = 0.672] or other cardiovascular parameters. These findings suggest that acute volume loading with saline does not improve V̇o(2peak) or cardiovascular responses to exercise in POTS, despite improvements in resting hemodynamic function.